Reply to my critics - Lorenz, Chris F.G. (Historein, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–> In this reply to my critics (Monika Bobako, Krzysztof Brzechczyn, Ewa Domańska, Juliusz Iwanicki, Aviezer Tucker, Hayden White). I am answering several critical arguments that have been formulated concerning my ‘Bordercrossings’. First, I dismantle the critique that I am subscribing to some version of ‘covering law explanation’. Second, I clarify in what – limited - sense I find Lakatos ideas concerning ‘scientific researchprogrammes’ fruitful for philosophy of history. The cognitive and political Doppelexistenz of theories in the human sciences explains why epistemological analyses always need to be complemented by practical analyses. Third, I defend my ‘double focus’ against the postmodern critique that my ‘internal realism’ is ‘powerblind’, and fourth, against the critique that ‘scientific history’ is ‘beyond politics’. Fifth and last I argue that in criticizing positions it is fruitful also to include the discussions about them in the critical argument. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Normale Tabelle"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –>